Overnutrition as a Risk Factor for Severity in Children with Covid-19: A Systematic Review - Toro-Ascuy, D (SOC CHILENA NUTRICION, BROMATOLOGIA & TOXICOLOGIA, 2024)
Introduction: Obesity is an ongoing pandemic that coincided with the COVID-19 pandemic, and it has been recognized as a significant risk factor for severe COVID-19 cases. This study aims to analyze the relationship between excess malnutrition and the severity of COVID-19 in minors through a systematic review. Methods: A systematic review was conducted following PRISMA guidelines. The search was carried out in PubMed/MEDLINE and SciELO databases using keywords, covering the period from 2020 to 2023. Studies of children and adolescents reporting age and nutritional status in English and Spanish were included. Studies with other pathologies, animal studies, pregnant women, and other reviews were excluded. The study was registered on the PROSPERO platform. Results: A total of 28 articles met the search criteria, of which 18 found a relationship between childhood obesity and increased severity, associated with longer hospital stays, mechanical ventilation requirements, and death. Additionally, out of 7 studies addressing Multisystem Inflammatory Syndrome in Children associated with COVID-19 (MIS-C), 3 found a relationship between obesity and the risk of developing MIS-C. Conclusion: Obesity is a risk factor for severe COVID-19 and an increased risk of developing and worsening MIS-C in children and adolescents. Identifying high-risk groups for severe COVID-19 could help guide hospital admissions and SARS-CoV-2 vaccination strategies.